2011
DOI: 10.1016/j.physletb.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic mass differences of SU(3) baryons within a chiral soliton model

Abstract: We investigate the electromagnetic mass differences of SU(3) baryons, using an "modelindependent approach" within a chiral soliton model. The electromagnetic self-energy corrections to the masses of the baryon are expressed as the baryonic two-point correlation function of the electromagnetic currents. Using the fact that the electromagnetic current can be treated as an octet operator, and considering possible irreducible representations of the correlation function, we are able to construct a general collectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…The corresponding formalisms and analyses in detail can be found in Ref. [23] and Ref. [24], respectively.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding formalisms and analyses in detail can be found in Ref. [23] and Ref. [24], respectively.…”
Section: )mentioning
confidence: 99%
“…In Ref. [23], the EM mass differences between baryons in the same isospin multiplet were analyzed within the χSM and the corresponding model parameters were fixed by the experimental data. Together with the isospin symmetry breaking from the mass difference of the up and down quarks, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Another well-known mass formula based on SUð3Þ F for the octet baryons is the Coleman-Glashow (CG) one [1]. Note that the masses of the octet baryons have been intensively studied in the calculations of the lattice QCD (LQCD) [2][3][4][5][6] as well as the theoretical models with the baryon wave functions [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Also we found that the coupling of antidecuplet N * to the πN channel is strongly suppressed. As the byproduct of our studies of the ground state baryons in the chiral quark-soliton model, we developed a method to calculate the electromagnetic mass differences in the octet and decuplet of baryons [53]. In this work we showed that the electromagnetic mass differences in the octet and the decuplet are related to each other due to the hedgehog symmetry of the model.…”
Section: Baryons From the Chiral Quark-soliton Picturementioning
confidence: 99%